Management of screening-detected stage I lung cancer - Osarogiagbon, Raymond U. (Journal of Thoracic Disease, 2016)
Easily the biggest development in the fight against lung cancer since the 1964 US Surgeon General’s report directly linked tobacco use to lung cancer, is the emergence of high-quality data clearly establishing the efficacy and cost-effectiveness of computed tomographic (CT)-screening as a means of improving lung cancer survival (1-4). Only tobacco control for primary prevention can have greater population-level impact on lung cancer mortality and survival statistics (5). Given the tight link between stage at treatment and survival, CT screening, by allowing early identification, leads to high lung cancer cure rates (3). Participation in screening is also a tremendous teachable moment that can potentially enhance smoking cessation, thereby contributing to primary (and secondary) prevention.